Leveraging integrated data for program evaluation: Recommendations from the field. (December 2022) - Zanti, Sharon; Berkowitz, Emily; Katz, Matthew; Nelson, Amy Hawn; Burnett, T.C.; Culhane, Dennis; Zhou, Yixi
Abstract: Use of administrative data to inform decision making is now commonplace throughout the public sector, including program and policy evaluation. While reuse of these data can reduce costs, improve methodologies, and shorten timelines, challenges remain. This article informs evaluators about the growing field of Integrated Data Systems (IDS), and how to leverage cross-sector administrative data in evaluation work. This article is informed by three sources: a survey of current data integration efforts in the United States (U.S.) (N=63), informational interviews with experts, and internal knowledge cultivated through Actionable Intelligence for Social Policy's (AISP) 12+ years of work in the field. A brief discussion of the U.S. data integration context and history is provided, followed by discussion of tangible recommendations for evaluators, examples of evaluations relying on integrated data, and a list of U.S. IDS sites with publicly available processes for external data requests. Despite the challenges associated with reusing administrative data for program evaluation, IDS offer evaluators a new set of tools for leveraging data across institutional silos. Highlights: Using linked administrative data benefits social program and policy evaluation. Over 93 data sharing and integration efforts currently exist across the U.S. 15 of these sites have data request processes for external evaluators. There are nine key recommendations for how evaluators can work with these sites.